2009
DOI: 10.1080/02713680802585938
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intravitreal Triamcinolone Acetonide in the Treatment of ExperimentalStaphylococcus epidermidisEndophthalmitis

Abstract: A standard clinical dose of intravitreal TA attenuates the clinical signs and tissue destruction in a rabbit model of Staphylococcus epidermidis endophthalmitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…We [3] reported that the kinetics and degrees of intraocular inflammation caused by B. cereus , S. aureus , and E. faecalis were highly variable, suggesting that the intraocular immune response is organism-dependent. This is clearly the case with relatively avirulent organisms such as S. epidermidis , which causes infection and inflammation in the eye only at high concentrations [32], [33]. Suggested development of therapeutics that target pattern recognition receptors must therefore not only account for organism-dependent differences in recognition, but also realistic timing of administration for different infection scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…We [3] reported that the kinetics and degrees of intraocular inflammation caused by B. cereus , S. aureus , and E. faecalis were highly variable, suggesting that the intraocular immune response is organism-dependent. This is clearly the case with relatively avirulent organisms such as S. epidermidis , which causes infection and inflammation in the eye only at high concentrations [32], [33]. Suggested development of therapeutics that target pattern recognition receptors must therefore not only account for organism-dependent differences in recognition, but also realistic timing of administration for different infection scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…8 Notably, the use of intravitreal triamcinolone attenuates the level of tissue damage caused by the inflammatory cascade in an S. epidermidis infection. 11 Under septic conditions caused by grampositive organisms, cytokines are released causing shock, 8 which may induce a localized disseminated intravascular coagulation (DIC) that causes retinal necrosis and macular infarction. A critical mediator of DIC is the release of a transmembrane glycoprotein called the tissue factor, which has a major role in the development of DIC in septic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…25 There were two preclinical studies examining the use of IVT triamcinolone acetonide in acute Staphylococcus epidermidis . 2627 There were one retrospective 28 and one pilot case series 29 looking at adjunctive IVT triamcinolone acetonide in addition to one retrospective case series looking at adjunctive IVT prednisolone 30 in acute endophthalmitis. There were 10 retrospective case series and 3 prospective randomized case series investigating the use of IVT dexamethasone.…”
Section: Methodsmentioning
confidence: 99%
“…26 However, in the presence of appropriate antibiotics, both studies reported that IVT triamcinolone attenuates the clinical signs of inflammation without impairing the therapeutic effect. 2627 Taking this a step further, the second study even found a reduction in pathologic damage associated with adjunctive IVT triamcinolone. 27 These results are similar with those reported in most studies investigating the effect of IVT dexamethasone in addition to IVT antibiotics in Staphylococcus epidermidis endophthalmitis.…”
Section: The Effect Of Ivt Corticosteroids In Preclinical Studies Of mentioning
confidence: 97%